Effects of 17β-estradiol on intracellular calcium changes and neuronal survival after mechanical strain injury in neuronal-glial cultures - Saitida Lapanantasin (2018)
The neuroprotective effects of 17β-estradiol (E2) were investigated using an in vitro model of traumatic brain injury in which cortical neuronal cultures were subjected to mechanical strain-injury. The rise in intracellular calcium ([Ca2+]i) following neuronal injury was reduced by addition of 10 or 100 nM E2 to the cultures immediately following injury. Neuronal damage was measured 24 h after injury by propidium iodide uptake and cell viability by carboxyfluorescein diacetate uptake. Addition of 1, 10, or 100 nM E2 to cell cultures immediately following injury decreased neuronal damage and increased neuronal viability compared to vehicle-treated neurons. These results demonstrate the neuroprotective activity of E2 in an in vitro model of neuronal injury, and suggest that such effects may be related to the ability of E2 to modulate [Ca2+]i. © 2006 Wiley-Liss, Inc.